Clinical investigation of patients with jaw deformity with comorbidities - Kiyohiro Kasahara; Teruhide Hoshino; Kei Sugiura; Yuki Tanimoto; Masahide Koyachi; Masae Yamamoto; Keisuke Sugahara; Masayuki Takano; Akira Katakura (SpringerOpen, 2022)
Abstract Background With improvements in the safety and stability of surgeries, the number of orthognathic surgeries is increasing. Most patients who undergo orthognathic surgeries are younger, and the number of orthognathic surgeries for patients with comorbidities is also increasing. We report a survey and clinical investigation of patients with comorbidities who underwent orthognathic surgeries at our department to improve the safety of orthognathic surgery. Results The participants included 296 men and 712 women, with a mean age of 28 years (13-19 years, n=144; 20-29 years, n=483; 30-39 years, n=236; 40-49 years, n=102; 50-59 years, n=39; ≥60 years, n=4). In total, 347 patients underwent one-stage Le Fort type I osteotomy and sagittal split ramus osteotomy (SSRO), 243 underwent SSRO, 287 underwent plate removal, 126 underwent genioplasty and plate removal, and five underwent other surgeries. In total, 529 patients had comorbidities (52%), including allergic diseases (n=220, 33%), respiratory diseases (n=107, 16%), neurologic and psychiatric diseases (n=69, 10%), gynecologic diseases (n=28, 4%), hematologic diseases (n=27, 4%), cardiovascular diseases (n=24, 4%), digestive diseases (n=22, 3%), metabolic and endocrine diseases (n=18, 3%), spinal diseases (n=11, 2%), ophthalmologic diseases (n=11, 2%), renal and urological diseases (n=9, 1%), and other diseases (n=117, 18%). Among the patients with comorbidities, 11 with hemorrhagic diatheses (hemophilia and von Willebrand disease), arrhythmia (atrioventricular block), psychiatric disease (adjustment disorder), and metabolic disease (diabetes) required cautious perioperative management. The patient with hemophilia was managed with regular low-dose recombinant factor VIII replacement therapy, and the patient with type I diabetes mellitus was administered continuous insulin infusion and sliding-scale insulin therapy; both patients had an uneventful course. Conclusions The study findings suggest that with the increase in orthognathic surgeries, oral and maxillofacial surgeons should adequately manage cases requiring cautious perioperative control and highlight the importance of preoperative screening. Despite the well-established safety and postoperative stability of orthognathic surgeries, oral surgeons should adopt appropriate additional preventive measures for patients with comorbidities.